PENINGKATAN PEREKONOMIAN PETANI KARET : PERSFEKTIF EKONOMI ISLAM - Darsono, Cipto (Journal Tafkirul Iqtishodiyyah, 2024)
Farming is a life support for farming communities, which manage various agricultural products, both in the food sector and smallholder plantation crops. One of the important commodities in this sector is rubber plants, which are found in many areas, including Lampung Province, which is one of the largest rubber producing areas in Indonesia. This research is a field research. Lampung Province is one of the regions in Indonesia where the majority of the population depends on rubber plantations for their living. This rubber plant is the main source of income that they rely on to meet their daily needs and pay their bills. In the current era of globalization, the rubber produced is not just natural rubber, but the result of the use of ever-increasing pressure. This affects the amount of elastic plastic produced. Many rubber plantations were established by local residents. For those who do not have their own plantations, they usually work to harvest rubber sap in gardens belonging to other people who have larger land. Rubber farmers are now experiencing an increase in the use of the resources they have to strengthen their economy. The significant increase in rubber prices in recent times also helps them to meet their family's basic daily needs.